The Complication and Safety Profile of Utilizing Kirschner Wires in Four Corner Fusions - Smith, Shelby R.; Dua, Karan; Wysocki, Robert W.; Fernandez, John J.; Cohen, Mark S.; Simcock, Xavier C. (Journal of Wrist Surgery, 2024)
Background Four corner fusion (4CF) can be performed using various techniques, each with its own efficacy and complication profile. Kirschner wires (K-wires) are a reliable and cost-effective method when performing 4CF.Purpose The purpose of this study was to determine the union rate and complication profile of utilizing K-wires when performing a 4CF.Materials and Methods A retrospective chart review was performed studying patients who underwent 4CF from a multisurgeon, single-institution database. Demographic data were collected, and functional outcomes were recorded including wrist range of motion (ROM), fusion rates, time to fusion, and complication rates. Continuous variables were compared via two-tailed t-tests, numerical data via one-way analysis of variance tests, and categorical data via Fisher's Exact test.Results In total, 141 patients underwent 4CF with K-wire fixation with an overall nonunion rate of 3.5% (5/141). Diabetics had a nonunion rate of 11% compared to 3% without diabetes (p = 0.28). Wrist ROM was significantly greater in patients who achieved bony union at 6 weeks after removal of hardware compared to the nonunion group (78.0 degrees ± 14.4 vs. 57.8 degrees ± 21.3, p < 0.05). There was no difference in wrist ROM between the two groups six months after hardware removal. There were no pin-related complications that required revision surgery.Conclusion 4CF utilizing K-wire fixation is a reproducible and cost-effective technique that results in good patient outcomes including bony union and functional wrist ROM. Smoking and diabetes did not significantly increase the risk of nonunion, and K-wire fixation can successfully be used in these patient populations.Level of Evidence Level IV (retrospective study).
Keywords: four corner fusion; partial wrist arthrodesis; surgical fixation; Kirschner wires; nonunion; outcomes; safety; complications